Resilience through sports: Ukraine and Latvia confront geopolitical challenges - Marina Kamenecka-Usova; Marina Kamenecka-Usova; Maxym Tkalych (Frontiers in Sports and Active Living)
This perspective article examines the response of the sports sector in Ukraine and Latvia to contemporary geopolitical challenges, particularly those arising from ongoing war in Ukraine. As tensions escalate, both nations have taken significant measures within the sports sector, adopting new legal frameworks and policies to align with national security goals. By analyzing recent legislative changes, sanctions, and collaborative efforts within international sports organizations, this article explores how Latvia and Ukraine's sports sectors are addressing political challenges. These efforts reflect a growing recognition of the need to uphold ethical standards, protect athletes, and use sports as a platform for resilience in the face of geopolitical threats.